Ethnic (in)equality in the public services of Kenya and Uganda - Simson, R (Oxford University Press, 2018)
The unfair distribution of public sector jobs is a common grievance in many societies, but arguably more so in ethnically polarized ones. Using census data from Kenya and Uganda, two countries with a history of ethnic conflict, this article examines how public employment is allocated in multi-ethnic societies by studying the correlates of holding public sector jobs. The results demonstrate that the public services of Kenya and Uganda are first and foremost comprised of educational elites with considerably higher average levels of educational attainment than across the labour forces at large. However, when education is controlled for, high-skilled women and candidates from less developed districts are more likely to work for the state than others. As a result, public sector jobs are more equitably distributed along gender, regional and ethnic lines than education alone would predict. I hypothesize that formal policies to promote regional equity in the provision of basic services in combination with affirmative action measures are contributing to creating comparatively inclusive public services.